Alexithymia in patients with psoriasis: a cross-sectional study from Ecuador - Cherrez-Ojeda, Iván; Vanegas, Emanuel; Felix, Miguel; Cherrez, Sofia; Suárez-Almendariz, Delia; Ponton, Johana; Preciado, Vladimir; Ollague-Cordova, Edgar; Loayza, Enrique (Psychology research and behavior management, 2019)
Alexithymia in Patients with Psoriasis: A Cross-Sectional Study from Ecuador
Gesehen am 08.04.2020